2023
DOI: 10.4314/as.v21i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazards associated with frozen fish marketing in Abeokuta metropolis in Ogun State, Nigeria

Abstract: This study assessed the occupational hazards and injuries associated with frozen fish marketers in Abeokuta metropolis, Ogun State of Nigeria. A two-stage sampling procedure was adopted in sampling 150 fish marketers from 10 popular markets within the study area. Data were elicited with the aid of an interview schedule and analyzed using descriptive statistics such as frequency distribution, percentage, mean, standard deviation, and Pearson’s Product Moment Correlation (PPMC) analytical tools. Results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fish stings and bites may also result in infections and subsequent amputation of fingers or toes. 24 The study found high prevalence of musculoskeletal disease conditions among the women in fishery sector as reported by more than two-third of the interviewed women. This includes, generalized body ache, back pain, neck pain, joint pain and stiffness, reduced range of movement, muscle weakness, numbness of limbs and physical deformity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Fish stings and bites may also result in infections and subsequent amputation of fingers or toes. 24 The study found high prevalence of musculoskeletal disease conditions among the women in fishery sector as reported by more than two-third of the interviewed women. This includes, generalized body ache, back pain, neck pain, joint pain and stiffness, reduced range of movement, muscle weakness, numbness of limbs and physical deformity.…”
Section: Discussionmentioning
confidence: 74%
“…Fish stings and bites may also result in infections and subsequent amputation of fingers or toes. 24…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural extension service which is one of the tools for agricultural development, serves as a source of information on new technologies for farming communities which when adopted can improve production, income and standard of living. Moreover, agricultural extension provides a channel through which farmers' problems could be identified for research and formulation of agricultural policies to the benefit of rural communities (Olaoye, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Nigeria, consumption of frozen fish is believed to be higher than other animal protein sources such as beef, mutton and chicken, among others. The massive importation of frozen fish has made Nigeria the largest importer of frozen fish in Africa (Olaoye et al, 2022;Abubakar et al, 2014) and ranking world's fourth largest importer-in volume terms (5.4% of global imports)-after China, Japan and The USA (Tall, 2023). Consequently, various frozen fish species are imported and sold in markets across northeastern Nigeria.…”
Section: Introductionmentioning
confidence: 99%